Food Systems: Pathways for Improved Diets and Nutrition. Issue 9 (30th July 2018) - Kennedy, Eileen; Kershaw, Meghan; Coates, Jennifer
Abstract: The United Nations has declared 2016–2025 as the Decade of Action on Nutrition. The emphasis of this decade is on alleviating malnutrition in all its forms. Food systems are 1 of 6 priorities for achieving this goal. This brief uses a food-systems approach to analyze the effects of agriculture production, commercialization, and sex on diet quality and nutrition.